Fraktalna interpretacja religijnej różnorodności - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2022)
The Fractal Interpretation of Religious Diversity (FIRR) is an original theological proposition of Perry Schmidt-Leukel, which was of great interest for theologians interested in interreligious dialogue. Thanks to FIRR, an intriguing opportunity was created to overcome the existing tensions and conflicts between religions, which turn out to be not only unnecessary, but even contrary to the nature of both the human mind and historically created religious systems. Dtespite the impression of novelty, the main intuition of FIRR was also present in the earlier interpretations of the multiplicity of religions, an example of which is the original anthropology of word elaborated by Walter Ong’s, which was recalled in the second part of the article.